Spatial spillover effects of the digital economy on high-quality development and carbon emissions: evidence from prefecture-level cities in Guangdong, China - Han, Pengxiang; Zheng, Chaohui (Frontiers in Climate, 2025)
The digital economy, as a sustainable and innovative mechanism for economic change, has emerged as a crucial national strategic driver for China’s attainment of high-quality development and low-carbon transition. Assessing the digital economy’s contribution to both high-quality development and carbon reduction, as well as evaluating the extent of its effects, can offer accurate decision-making assistance for prioritizing development sectors and optimizing resource distribution. This research utilizes the Entropy Weight TOPSIS approach and spatial autocorrelation analysis to investigate the spatiotemporal characteristics of the digital economy and high-quality development in Guangdong Province. A coupling coordination model evaluates the extent of coordination between the two, while a Spatial Durbin Model (SDM) is utilized to estimate the coefficients regarding the digital economy’s influence on both high-quality development and carbon emission reduction at the prefecture-level city size. The primary findings of the study are as follows: (1) Both the digital economy and high-quality development in Guangdong Province have progressively advanced, demonstrating notable spatial autocorrelation (Global Moran’s I ranging from 0.21 to 0.36, p < 0.01). Nonetheless, development r is uneven, with the Pearl River Delta region significantly outpacing other areas. (2) The coupling coordination level between the digital economy and high-quality development exhibits fluctuating stability and significant regional disparities. The Pearl River Delta, particularly Shenzhen and Guangzhou, consistently achieves a coordination quality level exceeding 0.90, whereas Meizhou and Maoming frequently fall below 0.20, indicating severe discoordination. (3) The digital economy has a substantial beneficial impact and spatial spillover effect on both high-quality development and carbon reduction. The SDM findings reveal that the digital economy exerts a substantial direct influence on high-quality development (coefficient = 0.4837, p < 0.01), while demonstrating a slight negative impact on carbon emissions (coefficient = −0.2012, p < 0.05), thereby affirming that its impact on high-quality development is predominantly more pronounced than its influence on low-carbon development. This report recommends focused ways to enhance the digital economy’s fundamental role in fostering high-quality development while also realizing its promise for low-carbon synergy.